The Emergence of Group Potency and Its Implications for Team Effectiveness - Woodley, Hayden J. R.; McLarnon, Matthew J. W.; O’Neill, Thomas A. (Frontiers in Psychology, 2019)
Much of the previous research on the emergence of team-level constructs has overlooked their inherently dynamic nature by relying on static, cross-sectional approaches. Yet theoretical arguments regarding emergent states have underscored the importance of considering time in understanding these states. Unfortunately, minimal work has been dedicated towards examining the dynamics of team emergent states. In the present research, we address this limitation by investigating the dynamic nature of group potency, a crucial emergent state, over time. Theory around the ‘better-than-average’ effect (i.e., an individual’s tendency to think he/she is better than the average person) suggests that individuals may have elevated expectations of their group’s potency early on, but may decrease over time as team members interact and members gain a more realistic perspective on their group’s potential abilities. In addition, as members gain experience with each other, they develop a shared understanding of team attributes. To investigate this, the current study used both latent growth and consensus emergence modeling to examine how group potency changed over time, and its relation with team effectiveness. Further, in accordance with the input-process-output framework, we investigated how the change in group potency mediated the relation between the team-level compositions of conscientiousness and extraversion personality traits and team effectiveness. We collected data from 337 first-year engineering students that comprised 77 project teams. Data were collected at three time points throughout an engineering design course. First, the results of the latent growth model suggested that group potency decreased, on average, following a linear trend over time. Second, we found that group consensus regarding group potency increased over time. Third, we found that teams’ initial group potency was a significant predictor of team effectiveness, but that change in potency was not significantly related to team effectiveness. Finally, we found that teams with higher mean-level conscientiousness – but not extraversion – had higher initial group potency. The indirect effect linking conscientiousness to team effectiveness, through initial potency, was also supported. Overall, the current study offers a unique understanding of the emergence of group potency.